The Chemistry of Thermal Food Processing Procedures - Micali, Maria; Fiorino, Marco; Parisi, Salvatore; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This Brief reviews thermal processes in the food industry - pasteurization, sterilization, UHT processes, and others. It evaluates the effects on a chemical level and possible failures from a safety viewpoint, and discusses in how far the effects can be predicted. In addition, historical preservation techniques - smoking, addition of natural additives, irradiation, etc. - are compared with current industrial systems, like fermentation, irradiation, addition of food-grade chemicals. The Brief critically discusses storage protocols - cooling, freezing, etc. - and packing systems (modified atmosphere technology, active and intelligent packaging). Can undesired chemical effects on the food products be predicted? This Brief elucidates on this important question. On that basis, new challenges, that currently arise in the food sector, can be approached.
Chemistry of Thermal Processing in the Food Industry: An Introduction -- Thermal Processing of Food Industries and Chemical Transformations -- Undesired Chemical Alterations and Process-related Causes: The Role of Thermal Control and the Management of Thermal Machines.
Keywords: Food science; Analytical chemistry; Manufactures; Food Science; Analytical Chemistry; Machines, Tools, Processes